PENGARUH RETURN ON ASSETS (ROA), LIKUIDITAS (CR), DEBT TO EQUITY RATIO (DER), DAN PRICE TO BOOK VALUE (PBV) TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Arya Syah Rendra, 13.05.51.0240; ., Taswan (Students Journal of Economic and Management, 2016)
The purpose of this study is to test the impact of financial ratio wich measured by Return on Assets, Liquidity, Debt to Equity Ratio, and Price to book value toward the companyâs stock return. This study uses quantitative approach with multiple linier regression method. This study uses sample consist of companies in manufacture sector which listed in indonesian stock exchange since 2011 up to 2013. The total of the sample which used in this study is 87 companies. This study found that in manufacture sector which listed in indonesian stock exchange since 2010 up to 2013; Return on Assets, Liquidity, Debt to equity ratio and Price to book value are simultaneous significantly affect stock return. Return on assets, liquidity, price to book value variables are significantly affect stock return and Debt to equity ratio is not significantly affect stock return. Keywords: Return on Assets, Liquidity, Debt to Equity Ratio, Price to book value, and stock return` Â